High-potential Working Fluids for Next Generation Binary Cycle Geothermal Power Plants - Zia, Jalal; Sevincer, Edip; Chen, Huijuan; Hardy, Ajilli; Wickersham, Paul; Kalra, Chiranjeev; Laursen, Anna Lis; Vandeputte, Thomas (General Electric Global Research, 2013)
A thermo-economic model has been built and validated for prediction of project economics of Enhanced Geothermal Projects. The thermo-economic model calculates and iteratively optimizes the LCOE (levelized cost of electricity) for a prospective EGS (Enhanced Geothermal) site. It takes into account the local subsurface temperature gradient, the cost of drilling and reservoir creation, stimulation and power plant configuration. It calculates and optimizes the power plant configuration vs. well depth. Thus outputs from the model include optimal well depth and power plant configuration for the lowest LCOE. The main focus of this final report was to experimentally validate the thermodynamic properties that formed the basis of the thermo-economic model built in Phase 2, and thus build confidence that the predictions of the model could be used reliably for process downselection and preliminary design at a given set of geothermal (and/or waste heat) boundary conditions. The fluid and cycle downselected was based on a new proprietary fluid from a vendor in a supercritical ORC cycle at a resource condition of 200C inlet temperature. The team devised and executed a series of experiments to prove the suitability of the new fluid in realistic ORC cycle conditions. Furthermore, the team performed a preliminary design study for a MW-scale turbo expander that would be used for a supercritical ORC cycle with this new fluid. The following summarizes the main findings in the investigative campaign that was undertaken: 1. Chemical compatibility of the new fluid with common seal/gasket/Oring materials was found to be problematic. Neoprene, Viton, and silicone materials were found to be incompatible, suffering chemical decomposition, swelling and/or compression set issues. Of the materials tested, only TEFLON was found to be compatible under actual ORC temperature and pressure conditions. 2. Thermal stability of the new fluid at 200C and 40 bar was found to be acceptable after 399 hours of exposure?only 3% of the initial charge degraded into by products. The main degradation products being an isomer and a dimer. 3. In a comparative experiment between R245fa and the new fluid under subcritical conditions, it was found that the new fluid operated at 1 bar lower than R245fa for the same power output, which was also predicted in the Aspen HSYSY model. As a drop-in replacement fluid for R245fa, this new fluid was found to be at least as good as R245fa in terms of performance and stability. Further optimization of the subcritical cycle may lead to a significant improvement in performance for the new fluid. 4. For supercritical conditions, the experiment found a good match between the measured and model predicted state point property data and duties from the energy balance. The largest percent differences occurred with densities and evaporator duty (see Figure 78). It is therefore reasonable to conclude that the state point model was experimentally validated with a realistic ORC system. 5. The team also undertook a preliminary turbo-expander design study for a supercritical ORC cycle with the new working fluid. Variants of radial and axial turbo expander geometries went through preliminary design and rough costing. It was found that at 15MWe or higher power rating, a multi-stage axial turbine is most suitable providing the best performance and cost. However, at lower power ratings in the 5MWe range, the expander technology to be chosen depends on the application of the power block. For EGS power blocks, it is most optimal to use multi-stage axial machines. In conclusion, the predictions of the LCOE model that showed a supercritical cycle based on the new fluid to be most advantageous for geothermal power production at a resource temperature of ~ 200C have been experimentally validated. It was found that the cycle based on the new fluid is lower in LCOE and higher in net power output (for the same boundary conditions). The project, therefore has found a new optimal configuration for low temperature geothermal power production in the form of a supercritical ORC cycle based on a new vendor fluid.